Delegated Legislation In Nigeria: Taming the Wilddog While it’s Still Early - Kingsley Osinachi N. Onu (LEGAL BRIEF, 2022)
Separation of power is strong pillar of a democratic government in the world. All arms of government are expected to confine themselves to their traditional responsibilities under the law. However, modern day realities have shown that a strict adherence to this sacred principle have the tendency to grid a government to a halt. Delegated legislation is the statutory donation of law making power to a person, organ or institution other than the legislature. This practice eases of huge legislative burden on the legislature, and it is an acceptable practice globally. This paper uses a desk-based approach to examine delegated legislation in Nigeria. The paper considers the concept of power and delegation; origin of delegated legislation; arguments for and against delegated legislation; publication and control of delegated legislation in Nigeria. The paper finds that a challenge associated with the growing pace of delegated legislation in Nigeria is the possible threat to the legitimacy to legislative enactments. It further finds that there is the challenge of control of delegated legislation in Nigeria due to the absence of a formal law on rule making like the Statutory Instruments Act, 1946 of England. It concludes by recommending that a law be enacted which will detail the guideline for the making of delegated legislation with strict provisions on scrutiny by the legislature or its committee.